Positive Solutions for Fourth-Order Singular p-Laplacian Differential Equations with Integral Boundary Conditions. (19th August 2010) - Zhang, Xingqiu; Cui, Yujun
Abstract : By employing upper and lower solutions method together with maximal principle, we establish a necessary and sufficient condition for the existence of pseudo-C 3 [ 0, 1 ] as well asC 2 [ 0, 1 ] positive solutions for fourth-order singularp -Laplacian differential equations with integral boundary conditions. Our nonlinearityf may be singular att = 0, t = 1, andu = 0 . The dual results for the other integral boundary condition are also given.